Evolução mineralógica e geoquímica multi-elementar de perfis de solos sobre lateritos e gossans na Amazônia - HORBE, Adriana Maria Coimbra (Universidade Federal do Pará, 2017)
With the aim of studying the genesis of soils developed on lateritic crusts, five profiles located in the region of Carajás (N5 and Igarapé Bahia procpects) as well as in Paragominas (Camoaí Mine) and Belém (Mosqueiro and Outeiro Beaches) municipalities all them located in Pará State, Brazil - have been selected. Based on the structures described in the profiles (N5, igarapé Bahia, Camoaí, Outeiro and Mosqueiro), it has been Possible to distinguish four differents horizons: fresh crust, partially-weathered crust, weathered crust and soil. The fresh crust is compact, vacuolar and composed of iron and aluminium oxyhydroxides. The partially-weathered crust is made up of fresh-crust relicts enclosed in yellowish or reddish clayey matrix, depending on the mineralogical composition of the fresh crust. The weathered crust is characterized by dominance of clayey matrix in relation to relicts, while the soil is composed exclusively of clayey material. The structures of the profiles show that the change from fresh crust to the overlying soil is gradual with volume expansion at the beginning of the fragmentat ion processes. This expansion is followed by the collapse of the profile as the relicts are entirely transformed into an earthy micro-aggregated material. The profiles of N5 and Igarapé Bahia prospects have been derived from a mature iron-aluminous crust, being characterized by the highest contents of kaolinite and hematite either in the crust or in the relícts. Gibbsite Al-goethite, anatasse and quartz are concentrated in the soil, which tends to be initially bauxitic, at the base of the profile, and to become kaolinite-rich toward the top. The mineralogical changes led to chemical modifications such as decrease in Fe2O3 and 8iO2 and increase in Al2O3, TiO2 and PF. The trace elements (V, Cr, Ni, R, Mo, Zr, Ga, Sc, Y, Mn, Cu and Pb besides Au in the profile of Igarapé Bahia) and REE's exhibit concentrations of 8 and Zr whereas the remaining ones tend to be progressively diluted from the crust toward the soil. The TiO2-mass balance shows that the transformation of the crust into soil took place by means of leaching of SiO2 and Fe2O3 in two profiles above mentioned, while Al2O2 underwent enrichment in the profile of N5 and leaching in the profile of igarapé Bahia. The soil formation from a mature aluminous crust in Camoaí differs from those described in the profile of Igarapé Bahia and of N5 in that it shows a decrease in gibbsite contents and an increase in kaolinite and quartz, whereas the verey low contents of ,hematite, goethite, and anatase do not present a characteristic distribution. The trace elements and the REE's, with contents much lower than those observed in the others profiles, show an increase in Zr and Mn toward the soil horizon and a dilution of the remaining ones. In the Camoaí, the transformation of the aluminous crust into soil, based on the TiO2-mass balance, took place through leaching of Al2O3 and enrichment in SiO2 and Fe2O3. In the profiles of Outeiro and Mosqueiro, deriveci from immature silicoferruginous lateritic crust the soil formation occurred by means of decreasing in hematite+goethite so that, in the resulting soil, quartz and kaolinite predominate. In consequence of this, a decrese in the Fe2O3 contents and an increase in SiO2 and Al2O3 have been observed in those profiles. The trace elements distribution presents, as in igarapé concentration of Zr and dilution of the remaining ones. Based on TiO2-mass balance, it could be noticed that the transformation of the crust in the profiles of Mosqueiro and Outeiro took place through leaching of Fe2O3, whereas SiO2 and Al2O3 underwent enrichment in the profile of Outeiro and Leaching in the one of Mosqueiro. On the basis of structures, mineralogical composition and geochemical data of the profiles, it has been possible to characterize an accentuated process of Fe loss in the iron-aluminous and in the silicoferruginous crust as well as Ai removal in the aluminous ones what led to soil generation. In the profiles derived from the iron-aluminous and the silicoferruginous crust, it has been observed substitution of hematite by Al-goethite, an intermediated segment - where there is predominance of gibbsite in the iron-aluminous profiles -- and presence of kaolinite at the top of both profiles. In every profiles, it has been reported quartz acumulation. The enrichment in quartz and the S1O2 being the latter likely come from externai sources -via vegetable-material decay - caused the neoformation of kaolinite from gibbsite in the profiles of N5, igarapé Bahia, and Camoaí. In the profiles of Mosqueiro and Outeiro the kaolinite presence in the soil is a consequence of its relative enrichment in the relation to the crust from which it has been derived. As a consequence of the mineralogical transformation, Fe has been leached from the profiles of N5, Igarapé Bahia, Mosqueiro, and Outeiro and Al from those of the Camoaí, as well as V, Cr, Mo, Ga, Sc, Cu, Pb and REErs. On the other hand, a strong enrichment in Zr and, in part, in 8 and Mn has been reported in every stud ied profiles. The transformations that caused the break down of the balance of the crusts, their desmantlement and comminution, forming relicts and a new clayey mineral phase, are consequence of organic matter influence which turns the environments conditions more acid and less oxidizing, in a process similar to that of weathering-profiles formation in humid tropical environments. The mineral and chemical difference observed between the profiles are consequence of compositional variation of the crusts which, in part, also reflect the degree of maturity of theirs. The mineralogical and geochemical characteristics of the soils in the investigated profiles allow us to correlate them to the Belterra Clay and, in consequence of this, to admit that Belterra Clay had an autochthonous origin in relation to the underlying lateritic crusts.